2020
DOI: 10.3390/ijerph18010246
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Assessments Instruments for Headache Disorders against the ICF Biopsychosocial Model of Health and Disability

Abstract: Headache disorders have a strong impact on sufferers’ lives. However, the “content” of assessment instruments addressing concepts, such as disability and quality of life (QoL), has not comprehensively been addressed. We searched SCOPUS for research papers in which outcome measures were used in adult populations of patients with migraine, tension-type headache (TTH), and cluster headache (CH). The content of single instruments was then mapped against the International Classification of Functioning, Disability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 184 publications
4
17
0
Order By: Relevance
“…Previous studies have used non-CH-specific questionnaires like HIT-6, MIDAS, HDI or MSQ 2.1 to measure disability in CH patients [ 3 , 4 ]. These studies have shown higher impairment in chronic and active episodic CH patients compared to eCH patients in remission or healthy controls [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have used non-CH-specific questionnaires like HIT-6, MIDAS, HDI or MSQ 2.1 to measure disability in CH patients [ 3 , 4 ]. These studies have shown higher impairment in chronic and active episodic CH patients compared to eCH patients in remission or healthy controls [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the excruciating character of CH attacks is well known, disability associated with the disorder has only recently come to focus. Due to the lack of CH-specific questionnaires, generic or migraine-specific questionnaires like the Headache Impact Test™ (HIT-6™), Migraine Disability Assessment (MIDAS), SF-12v2® Health Survey (SF-12v2®) or Migraine Specific Quality of Life Questionnaire Version 2.1 (MSQ v2.1) have mostly been used [ 3 ]. Although these studies have shown reduced quality of life and substantial disability in CH patients, it has been questioned whether CH-specific impairment is adequately captured or rather underestimated by these instruments [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the main implications is that psychiatric conditions should be considered in PTH management to tailor the treatment to patients [49]. Psychiatric disorders can be neglected in managing headaches in TBI patients; however, long-term management of PTH patients needs to consider a biopsychosocial model for patient treatment [195]. Further research is required to understand the neurobiological and neuropathological mechanisms contributing to secondary headaches following TBI and pave the way for more effective, patient-centered treatments.…”
Section: Discussionmentioning
confidence: 99%
“…For many years now, migraine has been positioned among the first places in the unenviable ranking of disability 8,9 , not only in adults but also in adolescents 10 , and the awareness of its importance as a social disease has now been established. Numerous studies on very large patient populations have shown in different geographical areas how the burden of migraine affects these patients widely at all latitudes when evaluated in terms of Health-Related Quality of Life, work productivity, healthcare resource utilization, cost of illness [11][12][13][14][15] .…”
Section: Burden Of Migraine Worldwidementioning
confidence: 99%